If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-4) + -6(0) = 0 Multiply 7 * -4 -28 + -6(0) = 0 Multiply -6 * 0 -28 + 0 = 0 Anything times zero is zero. -28 + 0 = 0 Combine like terms: -28 + 0 = -28 -28 = 0 Solving -28 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5(3c-2)=40-2c | | 8+41nx=3 | | -33=-7(2)-3 | | b-2.25=1 | | 3(-4x-4)=5+1x | | 9(3)+2(-7)= | | 9(0)+2(-8)= | | 2y+(y-3)+3=7y-(2y+4) | | 5x+17=4(3x+1) | | 145=-u+220 | | 9(4)+2(-5)= | | =1.2 | | 49-w=232 | | 3a+5b+11b-4b+2a-6= | | x+8y^3=0 | | 9y-(5y-4)=10y-(3y+2) | | inx^3=6 | | 45x-37y+87= | | 17-2p=4p | | 12x-11=64 | | -7(-6+9f)+3= | | 79-13= | | 9(-4z+5)-8= | | 3z^2-0.75=90 | | x+9=4(x-1)(x-1) | | 7+13x=11+13x | | 3(6x+8)=9x-16-x | | -8x-3=-48 | | 5x+2y=12findy | | y=x^2-2x-6y=4x+10 | | -16x^2+128x+2=0 | | (3x+2x+2+2x+2+5x+3)5= |